Association between prenatal factors and incidence of stunting in toddlers aged 0 – 23 months: A case-control study - Maula, Fanindy Ghanif; Ratnawati, Ratnawati; Zulaikhah, Siti Thomas (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Stunting is impaired growth caused by chronic malnutrition in the first thousand days of life divided into prenatal and postnatal period. The prenatal period starts from conception until before time of birth. It is caused by multifactor including dietary consumption, infectious diseases, maternal nutrition, socioeconomic factors, and environmental factors. Objective: This study aims to identify the correlation between prenatal factors and incidence of stunting in toddlers aged 0 – 23 months in the area of Puskesmas Guntur II (Guntur II Primary Health Care), Demak Regency.Methods: This was an analytic observational study with a case control design. Independent variables in this study were haemoglobin levels, iron tablet consumption behaviour, chronic energy deficiency (CED) status, maternal height, and antenatal care (ANC) frequency. Its sampling technique was a purposive and consecutive sampling. Its data were analysed by chi-square for bivariate analysis and logistic regression test for multivariate analysis.Results: The results of correlation between haemoglobin levels (p = 0,012; OR = 4,375; CI = 1,320 – 14,504), iron tablet consumption behaviour (p= 0,297; OR = 1,727; CI = 0,616 – 4,845), chronic energy deficiency status (p = 0,045; OR = 3,333; CI = 0,998 – 11,139), maternal height (p = 0,045; OR = 3,333; CI = 0,998 – 11,139), and ANC frequency (p = 0,067; OR = 2,667; CI = 0,924 – 7,699) with incidence of stunting . Risk factors for stunting based on multivariate analysis are chronic energy deficiency status (β = 1,703; p = 0,014; OR = 5,489; CI = 1,417 – 21,263) and frequency of ANC (β = 1,460; p = 0,018; OR = 4,307; CI = 1,287 – 14,417).Conclusion: The haemoglobin levels, maternal height, and CED status have significant correlation with incidence of stunting in toddlers aged 0 – 23 months. The CED status is the dominant risk factor of incidence of stunting in toddlers aged 0 – 23 months.